Construction of Three‐Dimensional In‐Zn‐Cd‐S Composite Materials and Their Visible‐Light Catalytic Performance. Issue 28 (25th July 2022) - Gong, Xiaoyu; Li, Zhiqiang; Yu, Minghui; Yu, Hao; Wang, Shuang; Shao, Hongyu; Cheng, Yuye; Dou, Minghao; Li, Danni; Li, Shenjie; Chen, Yanyan
Abstract: In this paper, a simple template‐free one‐step hydrothermal method was used to construct three‐dimensional In−Zn−Cd−S composite materials. By changing the ratio of In 3+ /(Zn 2+ +Cd 2+ ) and controlling the band gap of semiconductor, a novel efficient and stable photocatalyst was designed. In−Zn−Cd−S composite showed good adsorption capacity and photocatalytic activity. When In 3+ /(Zn 2+ +Cd 2+ ) was equal to 1/5, the photocatalytic activity of the composite was the highest. The degradation rate of RhB could reach 92.6 % within 5 min, and 97.6 % after 15 min. The results of cyclic experiments show that the IZCS‐4 catalyst has good cyclic performance and structural stability. According to the free radical capture experiment, the main effect of IZCS‐4 on the photodegradation of organic pollutants is H + and ⋅O 2− . The enhanced photocatalytic activity of the alloy semiconductor material is mainly because it can effectively separate the photogenerated carriers and successfully inhibit the photocorrosion of In2 S3 monomer. Abstract : A simple template‐free one‐step hydrothermal method was used to construct three dimensional In−Zn−Cd−S composite materials. By changing the ratio of In 3+ /(Zn 2+ +Cd 2+ ) and controlling the band gap of semiconductor, a novel efficient and stable photocatalyst was designed. In−Zn−Cd−S composite showed good adsorption capacity and photocatalytic activity. The results of cyclic experiments show that the IZCS‐4 catalyst has good cyclic performance and structural stability.